Direct quantification of precipitation behavior in engineering Al-Mg-Si alloy: A study using complementary small angle neutron scattering and transmission electron microscopy - Wangshu Zheng; Yifan Han; Lipeng Ding; Zhihong Jia; Lei Zhao; Ganting Yang; Yuyang Liu; Xuyang Feng; Haibiao Zheng; Yubin Ke; Qiang Guo (Next Materials)
Age-hardenable Al-Mg-Si alloys are widely used in engineering applications but still lack precise, quantitative insights into their precipitation behavior. In this study, we employed small-angle neutron scattering (SANS) to systematically investigate a typical Al-Mg-Si alloy under different aging conditions, complemented by site-specific transmission electron microscopy (TEM) analysis. Our results identify a clear precipitation sequence—Guinier-Preston (GP) zones → β'' → U2—and elucidate the underlying mechanisms through precipitation thermodynamics and kinetics. Both SANS and TEM measurements showed excellent agreement in precipitate size and volume fraction, offering valuable new perspectives on the precipitation kinetics of Al-Mg-Si alloys.